(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article studies the philosophical foundations of multiculturalism. A philosophical analysis of various theories of multiculturalism is carried out, modern philosophical bases of moral conditions of mutual conflict-free coexistence in a multicultural environment are revealed. On the substrate of multiculturalism, the philosophical concept of dialogue is grounded. The article explores and proves the philosophical significance and perspective of the multicultural model of integration of society and the state; multiculturalism allows to create and develop the structure of a national identity, where cultural identities of all citizens of the country are taken into account and preserved; multiculturalism removes barriers and lawlessness for representatives of different nationalities, provides them with equal access to the resources and opportunities of society and the state. The article proves that the policy of multiculturalism is the only option for creating and developing new interethnic relations in modern society. Key words: philosophical grounds, multiculturalism, culture, concepts, environment.